2014
DOI: 10.4102/sajhrm.v12i1.592
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of desired versus actual compensation practices in determining intrapreneurial behaviour

Abstract: Orientation: Past research recognises that human resources management practices may influence innovative behaviour, particularly as compensation systems can be used as a tool to increase intrapreneurial activity.Research purpose: The aim of this study is to determine the relationship between actual versus desired compensation practices and elevated intrapreneurial behaviour. This is in line with research that focuses on how to promote business innovation, rather than merely research whether innovation is desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…At the same time, these practices can prevent employees from leaving the company to start their own business (Hayton, 2005;Shulman et al, 2011). Madu and Urban (2014) also suggested that economic compensation is not the only factor to promote intrapreneurship, given that noneconomic rewards, such as growth opportunities, promotions and flexibility are also considered relevant to promote intrapreneurship. Other studies included different HR practices such as recruitment and communication as being relevant to IPB.…”
Section: Theoretical Framework 21 Hpws and Ipbmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, these practices can prevent employees from leaving the company to start their own business (Hayton, 2005;Shulman et al, 2011). Madu and Urban (2014) also suggested that economic compensation is not the only factor to promote intrapreneurship, given that noneconomic rewards, such as growth opportunities, promotions and flexibility are also considered relevant to promote intrapreneurship. Other studies included different HR practices such as recruitment and communication as being relevant to IPB.…”
Section: Theoretical Framework 21 Hpws and Ipbmentioning
confidence: 99%
“…Hayton et al, 2013;Tang et al, 2015;Zhang, and Jia, 2010;Zhang et al, 2008). However, as a response to the need to look further into the phenomenon of intrapreneurship, recent studies have focused their attention on analyzing the effect of HRM practices on intrapreneurship (see Christensen, 2005;Hayton, 2005, Madu andUrban, 2014). Some have placed the spotlight on single or specific practices (Castrogiovanni et al, 2011;Shulman et al, 2011;Madu and Urban, 2014;Teneau and Dufour, 2015) whilst others, like Hayton (2005), have conducted their analysis from a theoretical perspective, considering both the effect of isolated practices and the systemic effect of this bundle of HR practices.…”
Section: Introductionmentioning
confidence: 99%
“…Intrapreneurial Behavior is a voluntary and uncompelled behavior (Valsania et al, 2016), which is attendant to the individual level of analysis and a bottom-up technique for offering proactive initiatives by individual managers or employees (Åmo, 2010;Bosma et al, 2010). Intrapreneurial behavior could be crucial to the long-term survival of organizations and the economy at large, it is therefore essential to expedite the study of intrapreneurial behavior in the under-studied developing economies (Madu & Urban, 2014). Nonetheless studies on the intrapreneurial behavior of middle managers are scarce (Mustafa et al, 2016) in medium enterprises and particularly in the developing economies.…”
Section: Intrapreneurial Behavior (Ib)mentioning
confidence: 99%
“…This suggestion emerges due to a raft of arguments around the scant focus and attention often given in studying entrepreneurial pursuits and outcomes especially from a developing nation perspective (e.g. Molokwu et al , 2013; Madu and Urban, 2014; Urban, 2010).…”
Section: Introductionmentioning
confidence: 99%